The Flow of Influence: From Newton to Locke and Back - Ducheyne, Steffen (Rivista di storia della filosofia, 2009)
In this essay, the affinity between Locke's empiricism and Newton's natural philosophy is scrutinized. Parallels are distinguished from influences. I argue, pace G.A.J. Rogers, that Newton's doctrine of absolute space and time influenced Locke's Essay concerning Human Understanding (first edition: 1689, though bearing the year 1690 on its cover) from the second edition onwards. I also show that Newton used Lockean terminology in his criticism of Cartesianism. It is further argued that Locke's endorsement of corpuscularianism is merely methodological, i.e. he accepts it as a scientifically useful and psychologically intelligible paradigm, but not as a realist explanation of rerum natura. Like Newton, Locke was reluctant to accept the corpuscular theory of light. However, his reasons for doing so were different from those of Newton. This essay is divided into three parts: in the first, the stage is set by looking at the fundamentals of Locke's epistemology; in the second, several correspondences between Locke's and Newton's thought are explored and two cases of influence are argued for; and in the third, several arguments are provided for interpreting Locke's corpuscularianism as methodological.